Udbringes af riget. Om udleveringen af den første tyske emigrant til Gestapo under besættelsen. En mikrostudie i dansk neutralitets- og flygtningepolitik 1939/40 - Kirchhoff, Hans (Historisk Tidsskrift, 2013)
The Extradition of Waldemar Pötzsch: A Micro-Study in Danish Neutrality and Refugee Policy 1939-1940During Germany’s occupation of Denmark, 1940-1945, Danish authorities turned over 155 German emigrants and refugees, including a score of Jews, to the Gestapo. In the year 2000, in the context of an ongoing debate on collaboration during the war, this historical fact unleashed a media storm that prompted the government to launch a research project on Danish refugee policy from 1933 to 1945. The present article is part of its results.Waldemar Pötzsch was a German Social Democrat and secretary of a seamen’s organization in Bremen when, in 1933, he had to flee to Belgium after the Nazi takeover. He took part in organizing the resistance against Hitler’s regime from abroad and worked as a paid informer for British, French and Belgian intelligence agencies. The Gestapo was well aware of Pötzsch’s activities. It linked him to the sabotage group led by the Comintern agent Ernst Wollweber and demanded that he be turned over to them. In November 1938 Pötzsch was expelled from Belgium and in February 1939 he fled to Denmark with instructions from the British Secret Intelligence Service to carry out special tasks. In April he was arrested by the Danish police, presumably after a tip-off from the Gestapo, with which the Danish authorities worked very closely in investigating sabotage activities of the Wollweber group. In August Pötzsch was sentenced to eight months in prison to be followed by expulsion for spying on behalf of Great Britain. At this point the German embassy intervened, demanding that Pötzsch when released be extradited to Germany as an international terrorist. Meanwhile, the Gestapo was laying plans for kidnapping him, if diplomacy failed. To this very day it is still not clear whether Berlin really believed Pötzsch was a Wollweber saboteur, and why such a great effort was made to apprehend him.The Germans’ extradition demand created a serious dilemma for the Danish Ministries of Justice and Foreign Affairs. Where was neutrality, if you sent a British spy to Germany? Or where was due regard for Germany, if you released Pötzsch and put him on a boat to England? What was prescribed by international law, what was required by the national interest, and what consideration was due to the German emigrant himself? The problem was exacerbated by the outbreak of the war on Sept. 1, 1939, which put Denmark in the middle of tensions between the Great Powers. This became all too clear when Nazi propaganda proclaimed Pötzsch to be the main figure behind the SIS network, which the Nazis claimed was behind the attempt to murder Hitler on 8 November 1939. A German emigrant in a Danish prison was suddenly international politics.The core of the present article is an analysis of the considerations and decisions affecting Pötzsch’s fate that took place in the Ministries of Justice and Foreign Affairs. What considerations counted most? How important was the role allotted to international law and international agreements? How did fear of international terrorism affect the process? And what weight was given to humanitarian considerations? The diplomatic and legal documentary sources, upon which an answer to these questions is based, are used here for the first time.The analysis discerns three principal groups involved in the affair, each with a distinctive position. The police and prosecution authorities wanted to extradite Pötzsch, confident that the German accusations against him for maritime sabotage were true, and considering him in any case to be a criminal type undeserving of humanitarian help. At the Ministry of Justice the top legal experts likewise recommended extradition, although they found the evidence presented by the Germans flimsy, and had other reservations as well. In their opinion a legal case could be argued both for and against the German demand. In the end they resolved that the question was political and a matter to be dealt with by the Ministry of Foreign Affairs. Here there was no attempt to ignore that Denmark and Germany shared a common interest: Denmark’s desire to get rid of Pötzsch accorded with Germany’s desire to get hold of him. But the diplomats were less convinced than the legal experts that there was no chance of Pötzsch being able to claim that espionage was a political crime, thereby invoking the right of asylum. The decisive argument for the diplomats, however, was based on the crucial question of Denmark’s neutrality: to extradite a person who had spied for one of the parties to the war to another party to the war would jeopardize Danish neutrality, since such a person possessed information that could affect the war. The ministry of Foreign Affairs decided, therefore, in March 1940 not to turn Pötzsch over to the Germans, but to intern him in Denmark for the remainder of hostilities. That decision proved fatal for the German refugee when German forces invaded Denmark on 9 April. Even though the invasion took place in the form of a peaceful occupation that upheld the pretence of neutrality and left domestic governance, including legal jurisdiction, in the hands of the Danes, the fulcrum of real power was decisively shifted. On 13 April, without further ado, Pötzsch was turned over to the Gestapo. He was murdered in the concentration camp at Sachsenhausen in 1944.The positions taken by the three principal groups were congruent with the way refugee policy was practised in the 1930s. The police, charged with the practical implementation of a restrictive and inhumane policy, accepted entirely the Gestapo’s hostile portrayal of Pötzsch as a terrorist. The Ministry of Justice, which handled residence permits as well as the rejection and expulsion of refugees, took a middle position between the police and the ”softer” approach of the Foreign Ministry, where humanitarian arguments were not entirely dismissed. But the crux of the matter in deciding to intern Pötzsch was maintaining a balance between Great Britain and Germany, a compromise that was less than optimal for Germany, but did postpone an eventual conflict as long as possible. Humanitarian considerations played a secondary role at best. Nor did legal niceties and international law have any decisive significance in the process. Legal arguments served first and foremost as an alibi. The right of asylum had long been under attack in the struggle against international terrorism, and this infected the attitude of the actors in the decision-making process. None of them had any sympathy for Pötzsch, a proletarian with a shady and revolutionary past, a man who spied for pay. They saw him as a malicious person. No one found it worthwhile helping him, and no one found that his antifascist fight against Hitler’s dictatorship was reason to support him. For bourgeois Europe there was only a blurred line between Communism, civilian crime and political terror. It was only in the course of the war that the resistance movement made guerrilla tactics and revolutionary weapons such as sabotage legitimate.The decisive factor in interning Pötzsch for the remainder of the war was, therefore, the question of neutrality. Just how highly decisive it really was is shown by the dramatic turnabout when Denmark was invaded on 9 April 1940, and Great Britain as a counterbalance was out of the picture.Translated by Michael Wolfe